Market Response to Changes in Depreciation Accounting. - Comiskey, Eugene E. (The Accounting Review, 1971)
The article reports on the results of an analysis of the switch to straight-line depreciation from accelerated depreciation by several steel companies in 1968. Measuring the impact of the change in depreciation accounting is a relatively clear-cut and objective procedure. Attempting to determine the reasons for the switch to straight line is a much more elusive task. Many would speculate that the chief motive behind the change was the desire to increase profits. In general, an examination of the annual reports of the companies involved reveals that none offer this as the reason for the move to straight-line. The particular set of accounting alternatives used by a firm can be thought of as adding a unique "quality dimension" to the earnings. The more conservative the accounting alternatives, the higher are the "quality" of the earnings. Thus, the switch to straight line depreciation from accelerated depreciation would reduce the quality of the earnings and therefore also reduce the rate at which they are valued.